Qur’Anic and Biblical Prophets: Are They Really the Same People? - Leaman, Oliver (Al-Bayān, 2013)
It is a familiar Islamic doctrine that the prophets in the Jewish and Christian bibles are the same as those with the same name in the Qur’ān. They sometimes appear to be different since the bibles are not always accurate in their representation of the divine message to humanity. It could also be argued that if the prophets appear to be very different in the bibles from the prophets in the Qur’ān, then perhaps they are really not the same people. Sometimes the bibles are regarded as offering a corrupted view of the truth about the prophets and sometimes a less complete picture of them, which would explain the differences that are easy to detect. On the other hand, an argument is required to show that an apparent identity problem is only apparent, and we do not find one in the text of the Qur’ān itself.